PENGABDIAN KEPADA MASYARAKAT MEMBANGUN MOTIVASI DAN KREATIVITAS BERBISNIS DI DESA LUMBAN PEA TIMUR KABUPATEN TOBA - Anton Atno Parluhutan Sinaga; Robinhot Gultom; Sondang N. B. Marbun; Elperida J. Sinurat; Kristanty M. N. Nadapdap; Benget Rumahorbo; Nettina Samosir; Henri Saragih; Samuel V. B. H. Manurung; Maludin Panjaitan; Sahat P. Remus Silalahi; Toman Panggabean (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
Community Service aims to provide motivation and creativity and do business in Lumban Pea Timur Village, Toba Regency. In this case, the method used is the lecture, discussion, and question and answer method. Through this, many inputs were obtained, regarding the motives of the business being carried out, whether the business or business being carried out was the first attempt to be carried out, whether it had failed in carrying out the business and had been given training to open the business. Finally, through a question and answer session that the community is willing to do business, the motivation is high, but it is necessary to provide training to the community and assistance as well as working capital assistance to the local community.